New approach to calculate the denominator for the relative risk equation - Nor Azah Samat; Syafiqah Husna Mohd Imanm Ma’arof (Penerbit Universiti Kebangsaan Malaysia, 2016)
Disease frequency is used to measure the situation of the disease with reference to the population size and time period which is in a fractional form. The lower part of the fraction, known as denominator is the important part as it was used to calculate a rate or ratio. Since the disease frequency is based on a ratio estimator, the results are highly dependent upon the value of denominator. Therefore, the main aim of this paper was to propose a new method in calculating the denominator for the relative risk equation with the application to chikungunya disease data from Malaysia. The new method of calculating the denominator of the relative risk equation includes the use of discrete time-space stochastic SIR-SI (susceptible-infective-recovered for human population and susceptible-infective for vector population) disease transmission model instead of the total disease counts. The results of the analysis showed that the estimation of expected disease counts based on total posterior means can overcome the problem of expected counts estimation based on the total number of disease especially when there is no observed disease count in certain regions. The proposed new approach to calculate the denominator for the relative risk equation is suitable for the case of rare disease in which it offers a better method of expected disease counts estimation.